Genetic variants implicated in airway remodelling are risk factors for asthma severity in children and young adults. (24th May 2012) - Cunningham, J; Cheek, E; Tavendale, R; Mitra, A; MacGregor, D; Palmer, CNA; Smith, HE; Mukhopadhyay, S; Basu, K
Abstract : Introduction: Exacerbations affect quality-of-life, health care costs and represent a major cause of morbidity in children with asthma. To control the severity of asthma, physicians prescribe increasingly powerful regimes of medications in a tiered process according to BTS/SIGN guidelines. This process is often hit-and-miss with each patient responding uniquely, causing undue suffering and healthcare expenditure. We aim to identify predictive markers of asthma severity. Methods: Participants were recruited into the BREATHE study, a UK wide cross sectional study of gene environment interactions in children and young adults with asthma. 1539 children and young adults with physician-diagnosed asthma (age 3-22 years) from Sussex, England and Tayside and Dumfries, Scotland agreed to participate between 2004 and 2011. The dataset includes demographic, anthropometric and clinical details from 29 primary care practices and 8 secondary care asthma clinics. We have developed a global index of asthma severity through construction of a composite variable in the form of bronchodilator use adjusted asthma treatment class. Results: The homozygous C allele of CHI3L1rs4950928 is a risk factor for asthma-related hospital admissions (OR=1.39; 95% CI 1.02–1.88; P=.035). The co-dominant A allele of MMP9rs17576 is a risk factor for asthma-related exacerbations (OR=1.47; 95% CI 1.07–2.03; P=0.018), and asthma-related absence (OR=1.59; 95% CI 1.14–2.23; P=0.007). The co-dominant A allele of MMP9rs6073983 is protective for asthma-related exacerbations (OR=1.88; 95% CI 1.14–3.10;P=.014), asthma-related absence (OR=2.50; 95% CI 1.42-4.42; P=0.002) and increased asthma severity (OR=2.05; 95% CI 1.22–3.42; P=0.006). The co-dominant G allele of MMP12rs652438 increases the risk of asthma-related exacerbations (OR=1.51; 95% CI 1.05–2.18; P.026 and increased asthma severity (OR=1.74; 95% CI 1.03–2.96; P=0.040). The merged GSTM1 null/ GSTP1 rs1695/ GSTT1 null mutant variant increases the risk of asthma-related hospital admission (OR=1.51; 95% CI 1.04–2.26; P=0.046). Conclusion: Here we present clinically relevant findings on the impact of genetic variants in proteins influencing airway remodelling, on asthma severity in children and young adults with asthma. The presented variants increase the risk of asthma exacerbations and medication requirements in children and young adults. The study increases our understanding of the role of these molecules in causing asthma exacerbations, and influencing medication related asthma severity. The work could define susceptible population groups among children with asthma and help develop novel, personalised approaches for asthma management, providing economic benefits for an over-stretched healthcare system.